Strategi Peningkatan Produktivitas Padi Sawah Melalui Optimalisasi Peran Kelompok Tani (Studi Kasus Desa Karang Anyar) - prayoga, dayat; Nurcahyani, Marizha; Salqaura, Siti Sabrina (Universitas Medan Area, 2025)
This study aims to analyze the role of farmer groups in increasing the productivity of lowland rice farming. The study was conducted in Karang Anyar Village, Pegajahan District, Serdang Bedagai Regency in February 2025 with a sample of 14 people. The sample consisted of 12 members of the farmer group, 1 agricultural extension worker and 1 from the village head. The research method used is the SWOT method. This study shows that the SWOT matrix quadrant is in a (positive, positive) condition which indicates that the farmer group is in a strong and promising position. The recommended strategy given is progressive, meaning that the farmer group is in prime and stable condition so that it is very possible to continue to increase growth. The strategies that can be prioritized are the S-O strategies, including: (1) farmer groups can actively participate in extension and training to utilize the existence of PPL for agriculture, (2) farmer groups can continuously use quality seeds with assistance from the government, (3) farmer groups can use management that has been implemented on the production side from planting to harvesting to utilize government programs that support it.